Meta-synthesis of school leadership competencies to support learner-centered, personalized education - Richardson, Jayson W.; Khawaja, Sahar (Frontiers in Education, 2025)
This study analyzes the corpus of research on how K–12 school leaders foster deeper learning by creating learner-centered, personalized learning opportunities for students. We used the Leadership Competencies for Learner-Centered, Personalized Education developed by Jobs of the Future (2017) as our conceptual and analytical framework to analyze 42 peer-reviewed empirical articles. The findings detail how school leaders build structures to support learning-centered, personalized experiences for the students they serve.